Bauhaus Revisited: The Human Body as a Tool in Architectural Education (EAAE Annual Conference Proceedings, 2023)
The professional practice in architecture is becoming increasingly heterogeneous, specialised and strongly dominated by digitalisation. However, architecture teaching programmes are progressively concentrated in time. It is necessary to consider rigorously on the teaching content and to determine which disciplinary bases need to be maintained or recovered.